Flexible conductive composite material and preparation method and application thereof

By mixing graphene, carbon nanotubes with silicone rubber raw rubber and silane coupling agent, surface modification treatment and cross-linking reaction, flexible conductive composite materials with lower permeability threshold and higher mechanical properties were prepared, and the solution was solved In the prior art, the flexible sensor has low sensitivity, small range and poor repeat load capacity, which has achieved the efficient performance of the flexible piezoresistive sensor.

CN119410149APending Publication Date: 2025-02-11FUJIAN PROVINCIAL HIGHWAY DEV CENT +1

Patent Information

Application Number
CN202411514347.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

When used as the sensing layer of flexible sensors, existing flexible conductive composite materials have problems such as complex preparation methods, high seepage threshold, and poor bonding strength between fillers and polymers, resulting in low sensitivity, small range and poor repeat load capacity.

Method used

By mixing graphene, carbon nanotubes and polar organic solvents, a nanocarbon material dispersion is obtained, and mixed with silicone rubber raw rubber and silane coupling agent, surface modification treatment and cross-linking reaction are carried out to prepare a low-quality Flexible conductive composites with seepage threshold and higher mechanical properties.

Benefits of technology

The simplification and control of the preparation method are achieved, the seepage threshold of the flexible conductive composite material is reduced, and its mechanical properties are improved, so that the flexible piezoresistive sensor has a large range, high sensitivity and repeating load capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410149A_ABST
    Figure CN119410149A_ABST
Patent Text Reader

Abstract

The invention provides a flexible conductive composite material and a preparation method and application thereof, and belongs to the technical field of high polymer materials, and the preparation method comprises the following steps: mixing graphene, carbon nanotubes and a polar organic solvent to obtain a nano carbon material dispersion liquid; mixing raw silicone rubber, a silane coupling agent and the nano carbon material dispersion liquid, and carrying out surface modification treatment to obtain a nano carbon modified raw rubber mixed liquid; and mixing the nanocarbon modified raw rubber mixed solution with a cross-linking agent, and carrying out a cross-linking reaction to obtain the flexible conductive composite material. The prepared flexible conductive composite material has a low seepage threshold value and high mechanical performance, and after the flexible conductive composite material serves as a sensing layer of the flexible piezoresistive sensor, the flexible piezoresistive sensor can have a large measuring range and high sensitivity and repeated loading capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a flexible conductive composite material and a preparation method and application thereof. Background Art

[0002] Rubber bearings are a commonly used bridge bearing material, mainly composed of rubber and metal pads. The advantages of rubber bearings are good shock absorption and sound insulation effects, and good protection for bridges; the disadvantages are that they are easy to age, easy to be polluted, and have weak bearing capacity and are prone to disease. The detection of bearing defects of domestic bridges is mainly based on manual observation and instrument non-destructive testing, supplemented by methods such as image acquisition and image processing. At present, the instruments used in non-destructive testing are generally electronic sensors. Among them, flexible conductive composite materials formed by carbon nanomaterials with excellent conductivity and high molecular polymers (such as rubber, etc.) have good compatibility with the rubber layer of the bearing. The flexible sensors prepared with them can better adapt to the stress characteristics of the bearing and can effectively grasp the overall stress state of the bearing, which has attracted great attention from researchers.

[0003] However, the flexible conductive composite material formed by carbon nanomaterials and high molecular polymers still has the following technical problems to be solved when used as the sensing layer of the flexible sensor: First, in order to improve the sensitivity of the flexible sensor, a higher content of carbon nanomaterials needs to be added, but this will lead to a higher percolation threshold of the flexible conductive composite material; for example, Chinese patent CN 202310453809.9 discloses a carbon nanotube conductive composite material and its preparation method and application, the mass content of carbon nanotubes in the composite material is as high as 8%, although it has a higher sensitivity, but the higher percolation threshold causes the composite material to have poor mechanical properties and higher production costs. In order to reduce the percolation threshold of the high molecular polymer flexible composite material, the commonly used method in the field is to improve the dispersibility of the carbon material in the polymer matrix, such as Chinese patent CN201810101828.4 a silicone rubber / graphene / carbon nanotube nanocomposite material for electromagnetic shielding and its preparation method, this method requires first constructing a three-dimensional continuous graphene / carbon nanotube conductive network skeleton, and then backfilling silicone rubber, vulcanization and shaping, the preparation method is complicated and the conditions are difficult to control. Secondly, the sensor for bearing disease detection needs to have a large range, but the existing filled polymer flexible composite materials have poor bonding strength between the filler and the polymer, and are prone to damage and stress concentration under high pressure, resulting in the flexible sensors prepared therefrom being able to withstand low pressure and having a small range. At the same time, the poor bonding strength between the filler and the polymer will also lead to poor repeated load capacity of the flexible sensor. For example, Chinese patent CN 202210208630.2 discloses a three-dimensional porous carbon nanotube-graphene / PDMS composite material, a flexible strain sensor and its preparation. Although the flexible strain sensor prepared therefrom has good sensitivity in the low pressure range of 0 to 1 kPa, it has poor sensitivity under high pressure greater than 7 kPa.

[0004] It can be seen that the existing flexible conductive composite materials have the problem of complex preparation methods, and there are also technical problems such as high percolation threshold of the prepared flexible conductive composite materials and poor bonding strength between fillers and polymers. As a result, the flexible sensors prepared with flexible conductive composite materials as sensing layers have problems such as low sensitivity, small range and poor repeated load capacity. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a flexible conductive composite material which is simple and easy to control and has a lower percolation threshold and higher mechanical properties.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a flexible conductive composite material, comprising the following steps:

[0008] (1) mixing graphene, carbon nanotubes and a polar organic solvent to obtain a nanocarbon material dispersion;

[0009] (2) mixing silicone rubber raw rubber, a silane coupling agent and the nano-carbon material dispersion obtained in step (1), and performing surface modification treatment to obtain a nano-carbon modified raw rubber mixed solution;

[0010] (3) Mixing the nano-carbon modified raw rubber mixture obtained in step (2) with a cross-linking agent to carry out a cross-linking reaction to obtain a flexible conductive composite material.

[0011] Preferably, the mass ratio of graphene to carbon nanotubes in step (1) is 1:(1-3).

[0012] Preferably, in step (2), the ratio of the total mass of graphene and carbon nanotubes in the nano-carbon material dispersion to the mass of the silicone rubber raw rubber is (3.1-4.5):100.

[0013] Preferably, the temperature of the surface modification treatment in step (2) is 55 to 60° C., and the time of the surface modification treatment is 2 to 3 hours.

[0014] Preferably, the cross-linking agent in step (3) is selected from organic platinum.

[0015] Preferably, the temperature of the cross-linking reaction in step (3) is 15 to 40° C., and the time of the cross-linking reaction is 3 to 5 hours.

[0016] The present invention also provides a flexible conductive composite material prepared by the preparation method described in the above technical solution, comprising silicone rubber and graphene and carbon nanotubes dispersed in the silicone rubber, wherein the graphene and carbon nanotubes are combined with the silicone rubber through a silane coupling agent.

[0017] The present invention also provides a flexible piezoresistive sensor, wherein the sensing layer of the flexible piezoresistive sensor is the flexible conductive composite material described in the above technical solution.

[0018] Preferably, the flexible piezoresistive sensor comprises a pressure-sensitive sensing layer and a reinforcement layer and a packaging layer sequentially coated on the surface of the pressure-sensitive sensing layer;

[0019] The pressure-sensitive sensing layer comprises a first sensing layer, interdigital electrodes and a second sensing layer stacked from bottom to top, wherein the interdigital electrodes are connected to electrode wires; the material of the first sensing layer and the second sensing layer is the flexible conductive composite material according to claim 7.

[0020] Preferably, the reinforcement layer is made of fiber-reinforced silicone rubber.

[0021] The present invention provides a method for preparing a flexible conductive composite material, comprising the following steps: mixing graphene, carbon nanotubes and a polar organic solvent to obtain a nano-carbon material dispersion; mixing silicone rubber raw rubber, a silane coupling agent and the nano-carbon material dispersion, performing surface modification treatment to obtain a nano-carbon modified raw rubber mixed liquid; mixing the nano-carbon modified raw rubber mixed liquid with a cross-linking agent, performing a cross-linking reaction, and obtaining a flexible conductive composite material. The present invention mixes silicone rubber raw rubber, a silane coupling agent and a nano-carbon material dispersion, performs surface modification treatment, utilizes physical adsorption, chemical adsorption and chemical reaction between the silane coupling agent and the silicone rubber raw rubber and the nano-carbon material (i.e., graphene and carbon nanotubes) to change the surface properties of the nano-carbon material, improves the agglomeration phenomenon of the nano-carbon material in the silicone rubber raw rubber, and after the silicone rubber raw rubber is cured to form silicone rubber, the nano-carbon material is fully dispersed in the silicone rubber matrix. Moreover, since the silane coupling agent acts on the silicone rubber and the nano-carbon material in the form of physical adsorption, chemical adsorption and chemical bonding, the nano-carbon materials have a strong bonding ability, which can improve the mechanical properties of the flexible composite material such as toughness and strength, and thus enable the flexible composite material to withstand greater load pressure. In addition, since graphene and carbon nanotubes are used as fillers, the two-dimensional sheets of graphene and the one-dimensional structure of carbon nanotubes can construct a three-dimensional network structure in the silicone rubber, so that the nano-carbon material and the silicone rubber are closely connected and evenly interwoven. On the one hand, this structure is easier to form a conductive path and reduce the percolation threshold of the flexible composite material; on the other hand, it can improve the mechanical properties of the flexible composite material such as toughness and strength. The results of the embodiment show that the conductive threshold of the flexible conductive composite material prepared by the method provided by the present invention is as low as 3.1%; after the flexible conductive composite material is prepared into a flexible piezoresistive sensor, the maximum bearing load of the sensing element reaches 25.4KN; after 12 cyclic load tests, it has excellent resistance stability; the loading response time is 81ms, and the unloading response time is 105ms, which has excellent sensitivity. Therefore, the flexible conductive composite material prepared by the present invention has a lower percolation threshold and higher mechanical properties. When it is used as the pressure-sensitive sensing layer of a flexible piezoresistive sensor, the flexible piezoresistive sensor can have a larger measuring range, higher sensitivity and repeated load capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A flow chart of a method for preparing a flexible conductive composite material provided by an embodiment of the present invention;

[0023] Figure 2 A front view of a flexible piezoresistive sensor prepared according to an embodiment of the present invention;

[0024] Figure 3 A top view of the flexible piezoresistive sensor prepared by the present invention;

[0025] Figure 4This is a schematic diagram of a curing mold used in preparing a flexible conductive composite material in Example 1 of the present invention;

[0026] Figure 5 The resistivity-filling amount curves of the flexible conductive composite materials prepared in Examples 1 to 9 of the present invention and Comparative Examples 1 to 3;

[0027] Figure 6 This is a stress-strain curve diagram of the flexible piezoresistive sensor prepared in Example 10 of the present invention;

[0028] Figure 7 A resistance change rate-pressure curve diagram of the flexible piezoresistive sensor prepared in Example 10 of the present invention;

[0029] Figure 8 The cyclic loading system curve diagram of the cyclic loading test of the flexible piezoresistive sensor prepared in Example 10 of the present invention;

[0030] Fig. 9 This is a curve diagram of the change in sensor resistance under cyclic load of the flexible piezoresistive sensor prepared in Example 10 of the present invention;

[0031] Fig.10 This is a curve diagram of the resistance change-response time relationship of the flexible piezoresistive sensor prepared in Example 10 of the present invention. DETAILED DESCRIPTION

[0032] The present invention provides a method for preparing a flexible conductive composite material, comprising the following steps:

[0033] (1) mixing graphene, carbon nanotubes and a polar organic solvent to obtain a nanocarbon material dispersion;

[0034] (2) mixing silicone rubber raw rubber, a silane coupling agent and the nano-carbon material dispersion obtained in step (1), and performing surface modification treatment to obtain a nano-carbon modified raw rubber mixed solution;

[0035] (3) Mixing the nano-carbon modified raw rubber mixture obtained in step (2) with a cross-linking agent to carry out a cross-linking reaction to obtain a flexible conductive composite material.

[0036] The invention mixes graphene, carbon nanotubes and polar organic solvent to obtain nano carbon material dispersion.

[0037] In the present invention, the graphene is preferably a single-layer graphene and / or a multi-layer graphene, and the multi-layer graphene preferably has 2 to 5 layers. When the present invention uses the above-mentioned type of graphene, it has a larger specific surface area and is easier to form a conductive path in a polymer matrix. The present invention does not specifically limit the source of the graphene, and it can be prepared using conventional commercial products or preparation methods. In the present invention, the source of the graphene is preferably Shenzhen Suiheng Graphene Technology.

[0038] In the present invention, the carbon nanotubes are preferably single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The present invention has excellent electrical conductivity and mechanical properties when using the above-mentioned types of carbon nanotubes. In the present invention, the length of the carbon nanotubes is preferably 1 to 100 μm, more preferably 1 to 50 μm; the aspect ratio of the carbon nanotubes is preferably 100 to 5000, more preferably 100 to 500. The present invention does not specifically limit the source of the carbon nanotubes, and conventional commercially available products or preparation methods can be used for preparation. In the present invention, the source of the carbon nanotubes is preferably Shenzhen Suiheng Graphene Technology.

[0039] In the present invention, the mass ratio of the graphene to the carbon nanotubes is preferably 1:(1-3), more preferably 1:(1-2). The present invention controls the amount of graphene and carbon nanotubes within the above range, which can give full play to the complementary advantages of graphene and carbon nanotubes in morphology, and is more conducive to forming abundant conductive paths in the silicone rubber matrix at a lower addition amount of nanocarbon materials.

[0040] In the present invention, the polar organic solvent preferably includes tetrahydrofuran, isopropanol or ethanol. When the present invention adopts the above polar organic solvent, it is more conducive to the dispersion of graphene, carbon nanotubes and silicone rubber.

[0041] In the present invention, the polar organic solvent is used as a dispersion solvent for graphene and carbon nanotubes, and as a reaction solvent for subsequent surface modification treatment, and can be removed during the cross-linking reaction, so the present invention has no special limitation on the amount of the polar organic solvent. In the present invention, the ratio of the total mass of the graphene and carbon nanotubes to the volume of the polar organic solvent is preferably 0.2g:(200-300)mL, and more preferably 0.2g:(240-250)mL. The present invention controls the amount of the polar organic solvent within the above range, which can fully disperse the graphene and carbon nanotubes, and because the amount of graphene and carbon nanotubes added is related to the mass of the silicone rubber raw rubber, it can meet the subsequent surface modification treatment.

[0042] The present invention has no particular limitation on the method for mixing the graphene, carbon nanotubes and polar organic solvent. Conventional mixing methods can be used as long as the graphene and carbon nanotubes are fully dispersed in the polar organic solvent.

[0043] In the present invention, the method of mixing graphene, carbon nanotubes and polar organic solvents preferably includes: mixing graphene with polar organic solvents to obtain a graphene dispersion; mixing carbon nanotubes with polar organic solvents to obtain a carbon nanotube dispersion; mixing the graphene dispersion and the carbon nanotube dispersion to obtain a nanocarbon material dispersion.

[0044] The present invention preferably mixes graphene with a polar organic solvent to obtain a graphene dispersion.

[0045] The present invention has no special limitation on the concentration of the graphene dispersion liquid, which can be adjusted according to conventional methods. In the present invention, the concentration of the graphene dispersion liquid is preferably 0.00083 to 0.001 g / mL.

[0046] In the present invention, the method of mixing the graphene with the polar organic solvent is preferably magnetic stirring and ultrasound performed in sequence. The present invention can fully disperse the graphene in the polar organic solvent by adopting the above mixing method. In the present invention, the time of the magnetic stirring and ultrasound is independently preferably 1 to 3 hours, more preferably 1 hour.

[0047] In the present invention, the carbon nanotubes are preferably mixed with a polar organic solvent to obtain a carbon nanotube dispersion.

[0048] The present invention has no special limitation on the concentration of the carbon nanotube dispersion liquid, which can be adjusted according to routine. In the present invention, the concentration of the carbon nanotube dispersion liquid is preferably 0.00083 to 0.001 g / mL.

[0049] In the present invention, the method of mixing the carbon nanotubes with the polar organic solvent is preferably magnetic stirring and ultrasound performed in sequence. The present invention can fully disperse the carbon nanotubes in the polar organic solvent by adopting the above mixing method. In the present invention, the time of the magnetic stirring and ultrasound is independently preferably 1 to 2.5 hours, more preferably 1 hour.

[0050] After obtaining the graphene dispersion and the carbon nanotube dispersion, the present invention preferably mixes the graphene dispersion and the carbon nanotube dispersion to obtain a nano-carbon material dispersion.

[0051] The present invention has no particular limitation on the volume ratio of the graphene dispersion and the carbon nanotube dispersion, as long as the total mass concentration of graphene and carbon nanotubes in the nano-carbon material dispersion reaches 0.00083-0.001 g / mL.

[0052] In the present invention, the method for mixing the graphene dispersion and the carbon nanotube dispersion is preferably sequentially performed magnetic stirring and ultrasound. In the present invention, the time of the magnetic stirring and ultrasound is independently preferably 1 to 2.5 hours, more preferably 1 hour.

[0053] The present invention prepares a graphene dispersion and a carbon nanotube dispersion separately and then mixes the graphene dispersion and the carbon nanotube dispersion, which can improve the agglomeration caused by directly mixing the graphene and the carbon nanotubes in a polar organic solvent, and is more conducive to fully improving the dispersibility of the graphene and the carbon nanotubes in the polar organic solvent.

[0054] After obtaining the nano-carbon material dispersion, the present invention mixes silicone rubber raw rubber, a silane coupling agent and the nano-carbon material dispersion, and performs surface modification treatment to obtain a nano-carbon modified raw rubber mixed liquid.

[0055] The present invention has no special limitation on the type of the silicone rubber raw rubber, and conventional silicone rubber raw rubber can be used. In the present invention, the type of the silicone rubber raw rubber preferably includes cured silicone rubber RTV-2, liquid silicone rubber LSR or thermoplastic silicone rubber HTV. The present invention uses the above-mentioned silicone rubber raw rubber, which is more compatible with the support.

[0056] In the present invention, the ratio of the total mass of the graphene and carbon nanotubes to the mass of the silicone rubber is preferably (3.1-5.0): 100, and more preferably (3.1-4.0): 100. In the present invention, since the graphene and carbon nanotubes are well dispersed in the silicone rubber matrix, a rich conductive network can be formed in the silicone rubber matrix even with a small amount of nano-carbon material added.

[0057] In the present invention, the type of the silane coupling agent preferably includes one or more of aminosilane coupling agent (KH550, KH570), silicate coupling agent and epoxysilane coupling agent. The silane coupling agent used in the present invention can produce physical adsorption, chemical adsorption and chemical bonding with graphene, carbon nanotubes and silicone rubber matrix, which is beneficial to improve the dispersibility of graphene and carbon nanotubes in the silicone rubber matrix. The present invention has no special limitation on the source of the silane coupling agent, and conventional commercial products can be used. In the present invention, the source of the silane coupling agent is preferably Kangjin New Material Technology Co., Ltd.

[0058] In the present invention, the ratio of the total mass of the graphene and carbon nanotubes to the mass of the silane coupling agent is preferably 1:(20-25), and more preferably 1:(22-25). By controlling the amount of the silane coupling agent within the above range, the present invention is more conducive to fully dispersing the carbon nanotubes and graphene in the silicone rubber matrix.

[0059] The present invention has no special limitation on the method for mixing the silicone rubber raw rubber, the silane coupling agent and the nano-carbon material dispersion, and the conventional mixing method can be used to uniformly mix the above components. In the present invention, the method for mixing the silicone rubber raw rubber, the silane coupling agent and the nano-carbon material dispersion preferably includes: dissolving the silicone rubber raw rubber in a polar organic solvent to obtain a silicone rubber raw rubber solution, mixing the silicone rubber raw rubber solution, the silane coupling agent and the nano-carbon material dispersion by magnetic stirring, and the magnetic stirring time is preferably 0.5 to 1.5 hours, more preferably 1 hour.

[0060] The present invention first dissolves the silicone rubber in a polar organic solvent and then mixes it with the silane coupling agent and the nano-carbon material dispersion, which is more conducive to uniform mixing of the silicone rubber and other components. In the present invention, the polar organic solvent plays a role in promoting uniform mixing of the components, and needs to be removed during subsequent curing. Therefore, the volume of the polar organic solvent used to dissolve the silicone rubber in the polar organic solvent is not particularly limited in the present invention. It can be adjusted according to the amount of the silicone rubber so that the silicone rubber can be completely dissolved.

[0061] In the present invention, the temperature of the surface modification treatment is preferably 55-60°C, more preferably 56-58°C; the time of the surface modification treatment is preferably 2-3h, more preferably 2.5-3h. The present invention controls the temperature and time of the surface modification treatment within the above ranges, so that the silane coupling agent can fully modify the surface of graphene, carbon nanotubes and silicone rubber. The silane alkoxy group in the silane coupling agent is reactive to graphene and carbon nanotubes, and the organic functional group is reactive or compatible to silicone rubber. Therefore, the silane coupling agent is between the interface of silicone rubber and nano-carbon materials (graphene and carbon nanotubes), and can form a bonding layer, so that graphene and carbon nanotubes are evenly dispersed in the silicone rubber polymer network.

[0062] In the present invention, the surface modification treatment is preferably carried out under mechanical mixing, and the mechanical mixing preferably includes magnetic stirring and ultrasound performed in sequence. In the present invention, the time of the magnetic stirring is preferably 1 to 2.5 hours, more preferably 1 hour; the power of the ultrasound is preferably 300 to 600W, more preferably 600W; the time of the ultrasound is preferably 1 to 1.5 hours, more preferably 2 hours. The present invention can keep the graphene and carbon nanotubes in a dispersed state during the surface modification treatment through the above-mentioned mechanical mixing method, which is conducive to the full modification of the graphene and carbon nanotubes by the silane coupling agent.

[0063] After obtaining the nano-carbon modified raw rubber mixed solution, the present invention mixes the nano-carbon modified raw rubber mixed solution with a cross-linking agent to perform a cross-linking reaction to obtain a flexible conductive composite material.

[0064] The present invention has no special limitation on the source of the organic platinum, and any conventional commercially available product or conventional crosslinking agent that can promote the crosslinking reaction can be used. In the present invention, the crosslinking agent is preferably organic platinum; the organic platinum is preferably an olefin platinum curing agent, an alkyl platinum curing agent, a trace platinum curing agent or a platinum curing agent for addition-type silicone. The present invention uses the above crosslinking agent to promote the crosslinking reaction of silicone rubber raw rubber to obtain silicone rubber, thereby realizing the in-situ doping of graphene and carbon nanotubes in silicone rubber.

[0065] In the present invention, the mass ratio of the silicone rubber to the crosslinking agent is preferably (9-11):1, more preferably 10:1. By controlling the mass ratio of the silicone rubber to the crosslinking agent within the above range, the silicone rubber can be fully crosslinked.

[0066] The present invention has no particular limitation on the method for mixing the mixed solution with the crosslinking agent, and a conventional mixing method can be used to uniformly mix the components. In the present invention, the method for mixing the mixed solution with the crosslinking agent is preferably ultrasound, and the power of the ultrasound is preferably 250 to 600 W, more preferably 600 W; the time of the ultrasound is preferably 1 to 1.5 h, more preferably 1.2 to 1.5 h.

[0067] In the present invention, after the mixed liquid is mixed with the cross-linking agent, the solvent is removed and then poured into a curing mold to perform a cross-linking reaction to obtain a flexible conductive composite material.

[0068] The present invention has no special limitation on the method for removing the solvent. A conventional method for removing the solvent can be used to fully remove the polar organic solvent. In the present invention, the method for removing the solvent is preferably vacuum desolventization. The temperature of the vacuum desolventization is preferably 55 to 70°C, more preferably 65°C; the time of the vacuum degassing is preferably 1 to 2.5 hours, more preferably 2 hours.

[0069] In the present invention, the temperature of the cross-linking reaction is preferably 15 to 40° C., more preferably 25 to 35° C.; the time of the cross-linking reaction is preferably 3 to 5 hours, more preferably 3.5 to 4.5 hours. The present invention has no special limitation on the mold for the cross-linking reaction, and the mold can be selected according to the size of the required flexible conductive composite material.

[0070] In one embodiment of the present invention, the preparation flow chart of the preparation method of the flexible conductive composite material is preferably as follows Figure 1 As shown. Figure 1It can be seen that the present invention firstly prepares carbon nanotube dispersion and graphene dispersion by stirring and ultrasound respectively, mixes the two and then ultrasound obtains nano-carbon material dispersion; adds silicone rubber raw rubber solution to the nano-carbon material dispersion, adds silane coupling agent after mixing and stirring, adds cross-linking agent after stirring and ultrasound, removes solvent after mixing and dispersing, and then obtains flexible conductive composite material through cross-linking reaction.

[0071] The preparation method provided by the present invention is simple to operate and easy to control. The chemical combination between the silane coupling agent and the silicone rubber raw rubber and the carbon material is used to improve the agglomeration phenomenon in the graphene and carbon nanotube silicone rubber. The silicone rubber raw rubber is cured to form silicone rubber, so that the carbon nanotubes and graphene are fully dispersed in the silicone rubber matrix. Since the silane coupling agent is chemically combined with the silicone rubber and the carbon material, the bonding ability is relatively strong, and the mechanical properties such as the toughness of the flexible composite material are improved, so that it can withstand greater load pressure. In addition, since graphene and carbon nanotubes are used as carbon materials together, the two-dimensional sheet of graphene and the one-dimensional structure of carbon nanotubes can construct a three-dimensional network structure in the silicone rubber, and the nano-carbon material and the silicone rubber are cross-tightly connected and evenly interwoven. This structure is easier to form a conductive path, and the percolation threshold of the flexible composite material is reduced.

[0072] The present invention also provides a flexible conductive composite material prepared by the preparation method described in the above technical solution, comprising silicone rubber and graphene and carbon nanotubes dispersed in the silicone rubber, wherein the graphene and carbon nanotubes are combined with the silicone rubber through a silane coupling agent.

[0073] In the present invention, the percolation threshold of the flexible conductive composite material is preferably 3.0-4.5%, more preferably 3.1-4%. In the flexible conductive composite material provided by the present invention, carbon nanotubes and graphene form a three-dimensional network channel in silicone rubber, so that the percolation threshold of the flexible conductive composite material is within the above range.

[0074] The present invention also provides a flexible piezoresistive sensor, wherein the sensing layer of the flexible piezoresistive sensor is the flexible conductive composite material described in the above technical solution.

[0075] The present invention has no special limitation on the method for assembling the flexible conductive composite material as the pressure-sensitive sensing layer of the flexible piezoresistive sensor, and a conventional method for assembling a sensing layer may be used.

[0076] In the present invention, the flexible piezoresistive sensor preferably comprises a pressure-sensitive sensing layer and a reinforcement layer and a packaging layer sequentially coated on the surface of the pressure-sensitive sensing layer;

[0077] The pressure-sensitive sensing layer includes a first sensing layer, interdigital electrodes and a second sensing layer stacked from bottom to top, the interdigital electrodes are connected to electrode wires, and the materials of the first sensing layer and the second sensing layer are the flexible conductive composite materials described in the above technical solution.

[0078] In the present invention, the first sensing layer, the interdigital electrodes and the second sensing layer are preferably connected by pasting with conductive silver paint. The conductive silver paint used in the present invention has good conductivity.

[0079] In the present invention, the thickness of the first sensing layer and the second sensing layer is preferably 1.5-2.5 mm independently, and more preferably 2 mm; the thickness of the first sensing layer and the second sensing layer is preferably 1.5-2.5 mm independently, and more preferably 2 mm. In the present invention, the first sensing layer and the second sensing layer are preferably circular sensing layers, and the diameter of the circular sensing layer is preferably 15-25 mm, and more preferably 20 mm. The present invention is more conducive to improving the sensitivity of the sensor by controlling the size of the first sensing layer and the second sensing layer within the above range.

[0080] The present invention has no special limitation on the parameters of the interdigital electrodes, and any conventional interdigital electrodes can be used. In an embodiment of the present invention, the parameters of the interdigital electrodes are preferably Gap: 100 μm; 10 mm×10 mm.

[0081] In the present invention, the material of the reinforcement layer is preferably fiber reinforced silicone rubber. In the present invention, the model of the fiber reinforced silicone rubber is preferably Dow Corning PDMS184. The present invention can protect the pressure-sensitive sensing layer and improve the structural strength of the sensor by coating the reinforcement layer on the surface of the pressure-sensitive sensing layer.

[0082] The present invention has no special limitation on the material of the encapsulation layer, and a conventional encapsulation layer can be used. In the present invention, the material of the encapsulation layer is preferably glass fiber glue. The present invention can protect the reinforcing layer and improve the structural strength of the sensor by coating the reinforcing layer on the surface of the pressure-sensitive sensing layer.

[0083] In the present invention, the front view of the flexible piezoresistive sensor is preferably as follows Figure 2 As shown, the top view of the flexible piezoresistive sensor is preferably as shown Figure 3 shown.

[0084] The present invention has no special limitation on the preparation method of the flexible piezoresistive sensor, and a conventional preparation method of a flexible piezoresistive sensor can be used. In the present invention, the preparation method of the flexible piezoresistive sensor preferably includes:

[0085] (1) stacking a first sensing layer, interdigital electrodes and a second sensing layer in sequence to obtain a pressure-sensitive sensing layer through bonding, wherein the interdigital electrodes are connected through electrode wires;

[0086] (2) laying fiber-reinforced silicone rubber raw materials on the upper and lower sides of the pressure-sensitive sensing layer obtained in step (1), and heating and curing the layers to obtain a pressure-sensitive sensing layer covering the reinforcement layer;

[0087] (3) Pasting packaging materials on the upper and lower sides of the pressure-sensitive sensing layer of the coating reinforcement layer obtained in step (2) to obtain a flexible piezoresistive sensor.

[0088] In the present invention, the first sensing layer, the interdigital electrodes and the second sensing layer are preferably stacked in sequence and bonded to obtain the pressure-sensitive sensing layer.

[0089] In the present invention, the first sensing layer and the second sensing layer are preferably prepared by the method for preparing the flexible conductive composite material described in the above technical solution, which will not be described in detail here.

[0090] The present invention has no special limitation on the bonding method, and it only needs to bond and fix the first sensing layer, the interdigital electrodes and the second sensing layer stacked in sequence.

[0091] In the present invention, the bonding method preferably includes: first coating conductive silver paint on the upper surface of the first sensing layer, pasting the interdigital electrodes on the upper surface of the first sensing layer, then connecting electrode wires at both ends of the interdigital electrodes, and finally coating conductive silver paint on the lower surface of the second sensing layer and bonding it to the upper surface of the first sensing layer.

[0092] The present invention has no special limitation on the amount of the conductive silver paint, as long as it can achieve bonding and fixing of the first sensing layer, the interdigital electrodes and the second sensing layer.

[0093] After obtaining the pressure-sensitive sensing layer, the present invention preferably lays fiber-reinforced silicone rubber raw materials on the upper and lower sides of the pressure-sensitive sensing layer, and heats and cures the layers to obtain the pressure-sensitive sensing layer covering the reinforcement layer.

[0094] The present invention has no special limitation on the temperature and time of the heating and curing, and the temperature and time can be adjusted according to the type of the fiber-reinforced silicone rubber used, as long as the fiber-reinforced silicone rubber can be completely cured.

[0095] After obtaining the pressure-sensitive sensing layer of the coating reinforcement layer, the present invention preferably adheres packaging materials to the upper and lower parts of the pressure-sensitive sensing layer of the coating reinforcement layer to obtain a flexible piezoresistive sensor.

[0096] The present invention has no special limitation on the material of the packaging material, and conventional packaging materials can be used. In the present invention, the packaging material is preferably glass fiber glue, and the source of the glass fiber glue is preferably 3M. The present invention further enhances the fixing effect by coating the packaging layer outside the reinforcement layer.

[0097] Since the prepared flexible conductive composite material has a lower percolation threshold and higher mechanical properties, when it is used as a pressure-sensitive sensing layer of a flexible piezoresistive sensor, the flexible piezoresistive sensor can have a larger measuring range, higher sensitivity and repeated load capacity.

[0098] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0099] Example 1

[0100] A method for preparing a flexible conductive composite material, comprising the following steps:

[0101] (1) 0.1 g (3 to 5 layers) of graphene and 100 mL of tetrahydrofuran were magnetically stirred for 1 h, and then the ultrasonic power was set to 600 W for ultrasonic dispersion for 1 h to obtain a graphene dispersion with a concentration of 0.001 g / mL;

[0102] 0.1 g (parameter aspect ratio 150-250) of carbon nanotubes and 100 mL of tetrahydrofuran were magnetically stirred for 1 h, and then the ultrasonic power was set to 600 W and ultrasonically dispersed for 1 h to obtain a carbon nanotube dispersion with a concentration of 0.001 g / mL;

[0103] The graphene dispersion and the carbon nanotube dispersion are magnetically stirred for 1 hour and then ultrasonicated for 1 hour to obtain a nano-carbon material dispersion; the mass ratio of the graphene to the carbon nanotube is 1:1;

[0104] (2) 6.5 g of silicone rubber (room temperature vulcanized silicone rubber RTV-2) was dissolved in 100 mL of tetrahydrofuran, and then magnetically stirred with the nano-carbon material dispersion for 1 h, and then 4.6 g of KH550 coupling agent was added, stirred at 55.5° C. for 1 h, and surface modified by ultrasound at 600 W for 2 h to obtain a nano-carbon modified raw rubber mixed solution; the ratio of the total mass of graphene and carbon nanotubes in the nano-carbon material dispersion to the mass of the silicone rubber raw rubber was 3.1:100 (i.e., the filling amount was 3.1%); the ratio of the total mass of graphene and carbon nanotubes to the mass of the silane coupling agent was 1:23;

[0105] (3) The mixed solution and 0.65 g of crosslinking agent (KH550 coupling agent) were ultrasonically dispersed at 600 W for 2 h, vacuum degassed at 65 ° C in a vacuum drying oven for 2 h, and then poured into Figure 4 In the mold shown, the cross-linking reaction was carried out by heating at 35° C. for 4 h to obtain a flexible conductive composite material.

[0106] Example 2

[0107] A method for preparing a flexible conductive composite material, comprising the following steps:

[0108] (1) The difference from step (1) of Example 1 is that the mass of graphene is 0.1 g, the mass of carbon nanotubes is 0.15 g, and the mass ratio of graphene to carbon nanotubes is 2:3;

[0109] (2) The difference from step (2) of Example 1 is that the ratio of the total mass of graphene and carbon nanotubes in the nano-carbon material dispersion to the mass of the silicone rubber is 4:100 (i.e., the filling amount is 4%); the ratio of the total mass of graphene and carbon nanotubes to the mass of the silane coupling agent is 1:20;

[0110] (3) The same as step (3) of Example 1, to obtain a flexible conductive composite material.

[0111] Example 3

[0112] A method for preparing a flexible conductive composite material, comprising the following steps:

[0113] (1) The difference from step (1) of Example 1 is that the mass of graphene is 0.1 g, the mass of carbon nanotubes is 0.22 g, and the mass ratio of graphene to carbon nanotubes is 1:2.2;

[0114] (2) The difference from step (2) of Example 1 is that the ratio of the total mass of graphene and carbon nanotubes in the nano-carbon material dispersion to the mass of the silicone rubber is 5:100 (i.e., the filling amount is 5%); the ratio of the total mass of graphene and carbon nanotubes to the mass of the silane coupling agent is 1:21;

[0115] (3) The same as step (3) of Example 1, to obtain a flexible conductive composite material.

[0116] Example 4

[0117] A method for preparing a flexible conductive composite material, comprising the following steps:

[0118] (1) The difference from step (1) of Example 1 is that the mass of graphene is (0.1) g, the mass of carbon nanotubes is (0.3) g, and the mass ratio of graphene to carbon nanotubes is 1:3;

[0119] (2) The difference from step (2) of Example 1 is that the ratio of the total mass of graphene and carbon nanotubes in the nano-carbon material dispersion to the mass of the silicone rubber is 6:100 (i.e., the filling amount is 6%); the ratio of the total mass of graphene and carbon nanotubes to the mass of the silane coupling agent is 1:22;

[0120] (3) The same as step (3) of Example 1, to obtain a flexible conductive composite material.

[0121] Example 5

[0122] A method for preparing a flexible conductive composite material, comprising the following steps:

[0123] (1) The difference from step (1) of Example 1 is that the mass of graphene is 0.15 g, the mass of carbon nanotubes is 0.3 g, and the mass ratio of graphene to carbon nanotubes is 1:2;

[0124] (2) The difference from step (2) of Example 1 is that the ratio of the total mass of graphene and carbon nanotubes in the nano-carbon material dispersion to the mass of the silicone rubber is 7:100 (i.e., the filling amount is 7%); the ratio of the total mass of graphene and carbon nanotubes to the mass of the silane coupling agent is 1:25;

[0125] (3) The same as step (3) of Example 1, to obtain a flexible conductive composite material.

[0126] Example 6

[0127] A method for preparing a flexible conductive composite material, comprising the following steps:

[0128] (1) The difference from step (1) of Example 1 is that the mass of graphene is 0.15 g, the mass of carbon nanotubes is 0.37 g, and the mass ratio of graphene to carbon nanotubes is 1:2.47;

[0129] (2) The difference from step (2) of Example 1 is that the ratio of the total mass of graphene and carbon nanotubes in the nano-carbon material dispersion to the mass of the silicone rubber is 8:100 (i.e., the filling amount is 8%); the ratio of the total mass of graphene and carbon nanotubes to the mass of the silane coupling agent is 1:22;

[0130] (3) The same as step (3) in Example 1, to obtain a flexible conductive composite material.

[0131] Example 7

[0132] A method for preparing a flexible conductive composite material, comprising the following steps:

[0133] (1) The difference from step (1) of Example 1 is that the mass of graphene is 0.15 g, the mass of carbon nanotubes is 0.43 g, and the mass ratio of graphene to carbon nanotubes is 1:2.87;

[0134] (2) The difference from step (2) of Example 1 is that the ratio of the total mass of graphene and carbon nanotubes in the nano-carbon material dispersion to the mass of the silicone rubber is 9:100 (i.e., the filling amount is 9%); the ratio of the total mass of graphene and carbon nanotubes to the mass of the silane coupling agent is 1:24;

[0135] (3) The same as step (3) of Example 1, to obtain a flexible conductive composite material.

[0136] Example 8

[0137] A method for preparing a flexible conductive composite material, comprising the following steps:

[0138] (1) The difference from step (1) of Example 1 is that the mass of graphene is 0.2 g, the mass of carbon nanotubes is 0.45 g, and the mass ratio of graphene to carbon nanotubes is 1:2.25;

[0139] (2) The difference from step (2) of Example 1 is that the ratio of the total mass of graphene and carbon nanotubes in the nano-carbon material dispersion to the mass of the silicone rubber is 10:100 (i.e., the filling amount is 10%); the ratio of the total mass of graphene and carbon nanotubes to the mass of the silane coupling agent is 1:25;

[0140] (3) The same as step (3) in Example 1, to obtain a flexible conductive composite material.

[0141] Example 9

[0142] A method for preparing a flexible conductive composite material, comprising the following steps:

[0143] (1) The difference from step (1) of Example 1 is that the mass of graphene is 0.2 g, the mass of carbon nanotubes is 0.52 g, and the mass ratio of graphene to carbon nanotubes is 1:2.6;

[0144] (2) The difference from step (2) of Example 1 is that the ratio of the total mass of graphene and carbon nanotubes in the nano-carbon material dispersion to the mass of the silicone rubber is 11:100 (i.e., the filling amount is 11%); the ratio of the total mass of graphene and carbon nanotubes to the mass of the silane coupling agent is 1:25;

[0145] (3) The same as step (3) of Example 1, to obtain a flexible conductive composite material.

[0146] Comparative Example 1

[0147] A method for preparing a flexible conductive composite material, comprising the following steps:

[0148] (1) After dissolving 6.5 g of silicone rubber in 100 mL of tetrahydrofuran, the mixture was stirred with 10 g of KH550 coupling agent at room temperature for 1 h, and ultrasonicated at 600 W for 2.5 h to perform surface modification treatment to obtain a mixed solution; the ratio of the total mass of graphene and carbon nanotubes in the nano-carbon material dispersion to the mass of the silicone rubber raw rubber was 0:100 (i.e., the filling amount was 0%);

[0149] (2) The mixed solution and 0.65 g of a crosslinking agent (platinum curing agent) were ultrasonically dispersed at 600 W for 2 h, vacuum degassed at 65 ° C for 2 h in a vacuum drying oven, and then poured into Figure 4 In the mold shown, heating at 35° C. for 4 h was performed for cross-linking reaction to obtain a flexible composite material.

[0150] Comparative Example 2

[0151] A method for preparing a flexible conductive composite material, comprising the following steps:

[0152] (1) The difference from step (1) of Example 1 is that the mass of graphene is 0.025 g, the mass of carbon nanotubes is 0.025 g, and the mass ratio of graphene to carbon nanotubes is 1:1;

[0153] (2) The difference from step (2) of Example 1 is that the ratio of the total mass of graphene and carbon nanotubes in the nano-carbon material dispersion to the mass of the silicone rubber is 1:100 (i.e., the filling amount is 1%); the ratio of the total mass of graphene and carbon nanotubes to the mass of the silane coupling agent is 1:200;

[0154] (3) The same as step (3) of Example 1, to obtain a flexible conductive composite material.

[0155] Comparative Example 3

[0156] A method for preparing a flexible conductive composite material, comprising the following steps:

[0157] (1) The difference from step (1) of Example 1 is that the mass of graphene is 0.05 g, the mass of carbon nanotubes is 0.05 g, and the mass ratio of graphene to carbon nanotubes is 1:1;

[0158] (2) The difference from step (2) of Example 1 is that the ratio of the total mass of graphene and carbon nanotubes in the nano-carbon material dispersion to the mass of the silicone rubber is 2:100 (i.e., the filling amount is 2%); the ratio of the total mass of graphene and carbon nanotubes to the mass of the silane coupling agent is 1:100;

[0159] (3) The same as step (3) of Example 1, to obtain a flexible conductive composite material.

[0160] Comparative Example 4

[0161] A method for preparing a flexible conductive composite material, comprising the following steps:

[0162] (1) The difference from step (1) of Example 1 is that the mass of graphene is 0.1 g, the mass of carbon nanotubes is 0 g, and the mass ratio of graphene to carbon nanotubes is 0.1:0;

[0163] (2) The difference from step (2) of Example 1 is that the ratio of the mass of graphene in the graphene dispersion to the mass of the silicone rubber is 3:100 (i.e., the filling amount is 3%); the ratio of the mass of graphene to the mass of the silane coupling agent is 1:50;

[0164] (3) The same as step (3) of Example 1, to obtain a flexible conductive composite material.

[0165] Comparative Example 5

[0166] A method for preparing a flexible conductive composite material, comprising the following steps:

[0167] (1) The difference from step (1) of Example 1 is that the mass of graphene is 0 g, and the mass of carbon nanotubes is 0.1 g;

[0168] (2) The difference from step (2) of Example 1 is that the ratio of the mass of graphene in the carbon nanotube dispersion to the mass of the silicone rubber is 3:100 (i.e., the filling amount is 3%); the ratio of the mass of carbon nanotubes to the mass of the silane coupling agent is 1:50;

[0169] (3) The same as step (3) of Example 1, to obtain a flexible conductive composite material.

[0170] Test Example 1

[0171] The resistance of the flexible conductive composite materials prepared in Examples 1 to 9 and Comparative Examples 1 to 3 was measured using a digital multimeter to obtain a resistivity-filling amount curve of the flexible conductive composite material as shown in FIG. Figure 5 As shown. Figure 5 The filling amount of 3 to 11% corresponds to the resistivity values ​​of the flexible conductive composite materials prepared in Examples 1 to 9 in ascending order, and the filling amount of 0%, 1% and 2% corresponds to the resistivity values ​​of the flexible conductive composite materials prepared in Comparative Examples 1, 2 and 3 in ascending order. Figure 5 It can be seen that with the increase of graphene and carbon nanotube content, the resistivity of the composite material decreases, and the addition of graphene and carbon nanotubes as low as 3% can change the insulation properties of polymer silicone rubber materials and have a lower percolation threshold.

[0172] Example 10

[0173] A method for preparing a flexible piezoresistive sensor:

[0174] (1) Two pieces of the flexible conductive composite material prepared in Example 1 with a diameter of 20 mm and a thickness of 2 mm were taken as the first sensing layer and the second sensing layer respectively, and conductive silver paint was firstly coated on the upper surface of the first sensing layer, and the interdigital electrodes were pasted on the upper surface of the first sensing layer, and then the electrode wires were connected at both ends of the interdigital electrodes, and finally, conductive silver paint was coated on the lower surface of the second sensing layer, and was bonded to the upper surface of the first sensing layer to obtain a pressure-sensitive sensing layer;

[0175] (2) laying fiber-reinforced silicone rubber raw materials on the upper and lower sides of the pressure-sensitive sensing layer obtained in step (1), wherein the fiber-reinforced silicone rubber is Dow Corning PDMS184, which is composed of agent A (main agent), agent B (cross-linking agent) and fibers, and the main agent, the cross-linking agent and the short fibers are mixed in a mass ratio of 10:1:0.5 and magnetically stirred for 120 minutes; heating and curing at 40° C. for 12 hours to obtain a pressure-sensitive sensing layer coated with a reinforcement layer, wherein the thickness of the reinforcement layer is 2 mm;

[0176] (3) The pressure-sensitive sensing layer of the coating reinforcement layer obtained in step (2) is adhered with packaging material glass fiber glue on the upper and lower sides to obtain a flexible piezoresistive sensor.

[0177] Comparative Example 6

[0178] The difference from Example 10 is that the flexible conductive composite material prepared in Comparative Example 1 is used as the first sensing layer and the second sensing layer, and the remaining steps and parameters are the same as those of Example 10.

[0179] Comparative Example 7

[0180] The difference from Example 10 is that the flexible conductive composite material prepared in Comparative Example 4 is used as the first sensing layer and the second sensing layer, and the remaining steps and parameters are the same as those of Example 10.

[0181] Comparative Example 8

[0182] The difference from Example 10 is that the flexible conductive composite material prepared in Comparative Example 5 is used as the first sensing layer and the second sensing layer, and the remaining steps and parameters are the same as those of Example 10.

[0183] Test Example 2

[0184] (1) A universal testing machine was used to perform a compressive strength test on the flexible piezoresistive sensor prepared in Example 10. The test dimensions are shown in Table 1 below. Figure 6 is the stress-strain curve of the sensor.

[0185] Table 1 Sample dimensions of flexible piezoresistive sensor for compressive strength test

[0186]

[0187] pass Figure 6It can be seen that the sensor prepared by the present invention can adapt to large deformation.

[0188] When performing the compressive strength test, a multimeter was used to measure the resistance change of the flexible piezoresistive sensor prepared in Example 10, and a resistance change rate-pressure curve of the flexible piezoresistive sensor was obtained as shown in FIG. Figure 7 As shown. Figure 7 It can be seen that the maximum pressure load of the flexible piezoresistive sensor prepared by the present invention is 25.4KN. When the maximum load is reached, the resistance change of the sensor no longer increases, which is considered to have reached the pressure limit of the sensor. The sensor resistance-load curve shows that the accuracy of the sensor presents multiple changes.

[0189] The accuracy of the sensor is defined by S, as shown in formula (I):

[0190]

[0191] In formula (I): △R represents the resistance change value; R 0 Indicates the original resistance of the sensor; △P indicates the pressure change value.

[0192] from Figure 7 It can be seen that as the pressure increases, the sensor accuracy tends to be stable, and the sensor accuracy is 0.0114KN -1 , with good accuracy; this makes the sensing accuracy able to meet the needs of bearing internal force monitoring

[0193] (2) A cyclic loading test was performed on the flexible piezoresistive sensor prepared in Example 10 using a universal testing machine. The cyclic loading system was as follows: Figure 8 As shown in the figure, the maximum load of the cyclic loading setting is 20KN. The cyclic loading test is mainly used to determine the resistance stability of the sensor under cyclic loading. The test results are shown in Fig. 9 As shown, from Fig. 9 It can be seen that as the number of loading times increases, the resistance of the sensor tends to be stable, indicating that the sensor can stably monitor under repeated loading.

[0194] (3) A small pressure gauge was used to test the response time of the flexible piezoresistive sensor prepared in Example 10. The test method was to apply a 100N impact force vertically to the flexible piezoresistive sensor, and use a resistance multimeter to record the resistance change of the sensor, and draw a resistance change-response time relationship curve as shown in FIG. Fig.10 As shown. Fig.10 It can be seen that the loading response time of the flexible piezoresistive sensor prepared by the present invention is 81 ms, and the unloading response time is 105 ms, which has a faster response time.

[0195] It can be seen from the above results that the compounding of two nanocarbon-based conductive fillers in the present invention can effectively reduce the percolation threshold of the conductive filler in the conductive composite material compared to adding graphene or carbon nanotubes alone, thereby improving the range accuracy and range of the flexible piezoresistive sensor.

[0196] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a flexible conductive composite material, comprising the following steps: (1) mixing graphene, carbon nanotubes and a polar organic solvent to obtain a nanocarbon material dispersion; (2) mixing silicone rubber raw rubber, a silane coupling agent and the nano-carbon material dispersion obtained in step (1), and performing surface modification treatment to obtain a nano-carbon modified raw rubber mixed solution; (3) Mixing the nano-carbon modified raw rubber mixture obtained in step (2) with a cross-linking agent to carry out a cross-linking reaction to obtain a flexible conductive composite material.

2. The method for preparing the flexible conductive composite material according to claim 1, characterized in that: The mass ratio of graphene to carbon nanotubes in the step (1) is 1:(1-3).

3. The method for preparing the flexible conductive composite material according to claim 1 or 2, characterized in that: In the step (2), the ratio of the total mass of graphene and carbon nanotubes in the nano-carbon material dispersion to the mass of the silicone rubber raw rubber is (3.1-4.5):

100.

4. The method for preparing the flexible conductive composite material according to claim 1, characterized in that: The temperature of the surface modification treatment in step (2) is 55-60° C., and the time of the surface modification treatment is 2-3 hours.

5. The method for preparing the flexible conductive composite material according to claim 1, characterized in that: The cross-linking agent in step (3) is selected from organic platinum.

6. The method for preparing the flexible conductive composite material according to claim 1, characterized in that: The temperature of the cross-linking reaction in step (3) is 15 to 40° C., and the time of the cross-linking reaction is 3 to 5 hours.

7. The flexible conductive composite material prepared by the preparation method according to any one of claims 1 to 6 comprises silicone rubber and graphene and carbon nanotubes dispersed in the silicone rubber, wherein the graphene and carbon nanotubes are combined with the silicone rubber via a silane coupling agent.

8. A flexible piezoresistive sensor, wherein the sensing layer of the flexible piezoresistive sensor is the flexible conductive composite material according to claim 7.

9. The flexible piezoresistive sensor according to claim 8, characterized in that: The flexible piezoresistive sensor comprises a pressure-sensitive sensing layer and a reinforcement layer and a packaging layer sequentially coated on the surface of the pressure-sensitive sensing layer; The pressure-sensitive sensing layer comprises a first sensing layer, interdigital electrodes and a second sensing layer stacked from bottom to top, wherein the interdigital electrodes are connected to electrode wires; the material of the first sensing layer and the second sensing layer is the flexible conductive composite material according to claim 7.

10. The flexible piezoresistive sensor according to claim 9, characterized in that: The material of the reinforcement layer is fiber-reinforced silicone rubber.

Citation Information

Patent Citations

  • Electromagnetic shielding silicon rubber / graphene / carbon nanotube nano composite material and preparation method thereof

    CN108165019A

  • Three-dimensional porous carbon nanotube-graphene / PDMS composite material, flexible strain sensor and preparation

    CN114381124A

  • Carbon nanotube conductive composite material and preparation method and application thereof

    CN116496603A

Cited By

  • Flexible conductive composite material and preparation method and application thereof

    CN120966188A